2002
DOI: 10.1021/la025515d
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Coupling in Porcine Stomach Mucin

Abstract: We present data from small angle neutron scattering (SANS) on the polyelectrolyte side chain liquid crystalline phases of porcine stomach mucin. There is a polydomain nematic phase at concentrations above the point of brush overlap. Also, the proteoglycans were seen to orient under the influence of a magnetic field at concentrations below which the brushes do not extensively overlap. The field can be used to investigate the nature of the entanglement coupling between the molecules. The structure factor peak sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
87
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 34 publications
12
87
4
Order By: Relevance
“…Waigh et al found evidence of a highly organized structure, discussed in terms of polydomain nematic phases above some critical semi-dilute concentration, and polyglycan orientation under magnetic field at lower concentration [62]. They also determined the cross-sectional radius and length of the mucin, obtaining results in agreement with Hong et al…”
Section: Small-angle Neutron Scattering Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…Waigh et al found evidence of a highly organized structure, discussed in terms of polydomain nematic phases above some critical semi-dilute concentration, and polyglycan orientation under magnetic field at lower concentration [62]. They also determined the cross-sectional radius and length of the mucin, obtaining results in agreement with Hong et al…”
Section: Small-angle Neutron Scattering Methodssupporting
confidence: 52%
“…When investigating relationships between physical properties and molecular structure, the determination of molecular organization within complex systems is fundamental; small-angle neutron scattering (SANS) -a powerful, non-destructive technique that probes organizational structure on a 1-200 nm lengthscale -can be easily applied for the study of delicate biological materials, although most studies published to date have focused on mucin [61][62][63][64][65].…”
Section: Small-angle Neutron Scattering Methodsmentioning
confidence: 99%
“…However, given the strong correlation with the sharp rise in pH in the presence of H. pylori and the subsequent change in rheology in nearly exact parallel with the pH dependence of every measure of viscoelastic response previously established (26), the results here indicate that the dominant effect of H. pylori on gastric mucin rheology is that due to pH elevation. Small differences in moduli are related to use of HCl which leads to different ionic strength than the buffers used in previous studies (26,49,50).…”
Section: Discussionmentioning
confidence: 89%
“…The detailed macromolecular structure of mucin has previously been investigated using highresolution scattering techniques, such as synchrotron SAXS, 60,61,62 SANS, 61,26,63 , static light scattering (SLS) and DLS 64 to compare the properties of mucin samples with different biological origins and preparation methods. The cylindrical model and the more recent double-globular comb model have therefore been used to account for the complex structure of mucin.…”
Section: Polysaccharide Charge Is a Fundamental Component Of Interactmentioning
confidence: 99%
“…The cylindrical model and the more recent double-globular comb model have therefore been used to account for the complex structure of mucin. 60,63,64 Aqueous solutions of bovine submaxillary mucin studied by SAXS displayed an expanded chain conformation at low concentrations (1.4-3.6 mg/mL) but a Gaussian chain conformation at higher concentrations (> 7 mg/mL). 62 More recent studies have addressed the impact of concentration on the structure of mucin and the existence of a coil overlap concentration (c*), along with other parameters as measured by a combination of SLS, DLS and rheology, concluding that c* = 1.54 mg/mL in water.…”
Section: Polysaccharide Charge Is a Fundamental Component Of Interactmentioning
confidence: 99%